Pelatihan Pembuatan Masker Wajah Tipe Peel-Off dari Herba Lumut Hati Marchantia paleacea dan Daun Teh Hijau kepada Mitra Posbindu - Dicki Bakhtiar Purkon; Mimin Kusmiyati; Elvi Trinovani; Zahwa Ainunnisya Nur Aisyah; Nizella Syahla; Ansyirohanisa Ansyirohanisa; Vindi Nur Amalia; Faizah Min Fadhlillah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Peel-off type facial skin mask preparations from herbal/synthetic ingredients can have the advantages of being easily removed, such as elastic membranes, improving hydration of the skin, treating wrinkles, aging, and acne, shrinking pores, moisturizing the skin, and relaxing facial muscles. Posbindu partner cadres in the working area of Puskesmas Pasirkaliki, Cimahi City, feel that there is still a lack of understanding and skill level in making simple cosmetic preparations from herbal ingredients, especially peel-off type facial skin mask preparations. Thus, we, as an extension team from the Community Partnership Program (PKM) grant scheme, strive to provide booklets, counseling on various facial skin health materials, and training assistance in making peel-off type facial skin masks with simple formulations of a combination of Marchantia paleacea liver moss herbaceous plants and green tea leaves to posbindu partner cadres in the Pasirkaliki Puskesmas Working Area, North Cimahi Village, Cimahi City. The mixed results of this community service activity indicate that there are benefits, such as a significant increase in the level of health understanding in the results of pre-test and post-test evaluations of various health education that have been provided, including the importance of utilizing peel-off type facial skin mask preparations from traditional herbal ingredients and Posbindu partner cadres as agents of change are expected to convey health information and skills that obtained so that it can be conveyed to the immediate family and the rest of the community in general